Quality of Government Innovation Public Safety Center (PSC) 199 in Soppeng Regency - Amin, Muhammad As’ad; Thaha, Rasyid; Irwan, Andi Lukman (Journal La Bisecoman, 2023)
Government innovation in health services is one of the autonomy affairs that has a lot of room for innovation because the challenges of health services are very complex, that complexity produces various ideas in addition to producing novelty in a government innovation update, among others, in improving services to the community both in the central government and local governments. At the local level, for example, there are currently several city districts that have succeeded in holding administrative innovations, to improve government administration, and can serve the community well. But the performance of local governments in implementing public services in improving the achievement of local government development. This research uses qualitative methods. Data collected through observation and documentation and developed through interviews. The results of this study indicate that the quality of Soppeng Regency local government innovation in health services for 24 hours can be categorized as good and maximum service, because it is based on the rules of the government itself and perceived service to community leaders and service users (Patients).